Integrated Strategies for a Counseling Culture: Adaptation of Evidence-Based Interventions - Nurmawati (Universitas Negeri Semarang, 2022)
Abstract. The importance of adapting interventions to the implementation of counseling culturally has been recognized. Although a systematic process of cultural adaptation is not yet available in ethno-culture. There are no specific instructions on how to adapt interventions that align with cultural beliefs. In this case the presenter presents an integrated strategy that operationalizes the adaptation process by explaining specific practice instructions on how to align interventions with specific cultural beliefs. Methods: this strategy integrates concept mapping, intervention, and uses mixed methods to collect data related to people's cultural beliefs and values ​​related to the problems experienced. On the acceptance of evidence-based interventions that target the problem and aspects of the intervention that should be modified to increase conformance to cultural beliefs. A step-by-step protocol is described to guide the implementation of integrated strategies for cultural adaptation of counseling. Conclusion: the power of an integrated strategy relies on using the concept and intervention mapping approach to establish step-by-step service protocols to be effectively culturally adapted so as to increase service effectiveness and reduce biased counselling.